Oral Inoculation of Chickens with a Candidate Fowl Adenovirus 9 Vector - Deng, Li (American Society for Microbiology, 2013)
Fowl adenoviruses (FAdVs) are a potential alternative to human adenovirus-based vaccine vectors. Our previous studies demonstrated that a 2.4-kb region at the left end of the FAdV-9 genome is nonessential for virus replication and is suitable for the insertion or replacement of transgenes. Our in vivo study showed that the virus FAdV-9Δ4, lacking six open reading frames (ORFs) at the left end of its genome, replicates less efficiently than wild-type FAdV-9 (wtFAdV-9) in chickens that were infected intramuscularly. However, the fecal-oral route is the natural route of FAdV infection, and the oral administration of a vaccine confers some advantages compared to administration through other routes, especially when developing an adenovirus as a vaccine vector. Therefore, we sought to investigate the effects of FAdV-9 in orally inoculated chickens. In the present study, we orally inoculated specific-pathogen-free (SPF) chickens with FAdV-9 and FAdV-9Δ4 and assessed virus shedding, antibody response, and viral genome copy number and cytokine gene expression in tissues. Our data showed that FAdV-9Δ4 replicated less efficiently than did wtFAdV-9, as evidenced by reduced virus shedding in feces, lower viral genome copy number in tissues, and lower antibody response, which are consistent with the results of the intramuscular route of immunization. Furthermore, we found that both wtFAdV-9 and FAdV-9Δ4 upregulated the mRNA expression of alpha interferon (IFN-α), IFN-γ, and interleukin-12 (IL-12). In addition, there was a trend toward downregulation of IL-10 gene expression caused by both viruses. These findings indicate that one or more of the six deleted ORFs contribute to modulating the host response against virus infection as well as virus replication in vivo.